KONTRIBUSI BALAI LATIHAN KERJA DALAM PEMBERDAYAAN KETERAMPILAN KERJA PADA USIA ANGKATAN KERJA DI KOTA SEMARANG - Rahman Alamsyah Atmaja; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
This study aims to analyze the role of the Technical Implementation Unit of the Job Training Center (BLK) of Semarang City in empowering work skills for the working-age community. This research uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation with informants consisting of the Head of BLK, training participants, and training alumni. The data sources used were primary data and secondary data. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the Job Training Center of Semarang City has a strategic role in improving skills, competence, and community independence through competency-based training programs. The training programs have a positive impact on participants in obtaining jobs and starting independent businesses. In addition, BLK also supports gender equality through training programs that provide equal opportunities for both women and men. However, there are still several obstacles such as limited facilities and infrastructure and job placement systems that are not yet optimal. Therefore, it is necessary to improve facilities, strengthen cooperation with industries, and develop training curricula in accordance with labor market needs.